Diversity of lipid profiles of Symbiodiniaceae under temperature and nutrient stress - La Motta, Laura M.; Padula, Matthew P.; Sommer, Brigitte; Camp, Emma F.; Matthews, Jennifer L. (Frontiers in Protistology, 2024)
Lipid-based survival mechanisms allow microalgae to occupy wide geographical ranges and survive abiotic stress. The protist Symbiodiniaceae are globally distributed from temperate to tropical environments, and establish mutualisms with numerous hosts, including cnidarians. The ability for these dinoflagellates to maintain cellular function under wide ranging environmental conditions will influence the survival and geographic distribution of their hosts. One mechanism that microalgae utilize to adapt to environmental changes is lipid remodeling, such as increased saturation of membranes to maintain the structural integrity under temperature changes, and lipid accumulation when nutrient availability decreases. Whether Symbiodiniaceae utilize lipid remodeling to adapt to sublethal environmental change is yet to be resolved. This study examines the effects of temperature (16 ºC to 31 ºC), and nitrogen (N) and phosphorus (P) availability, on the lipid composition and physiology of cultured Symbiodiniaceae (from genera Breviolum, Cladocopium and Durusdinium) isolated from temperate or tropical environments. Glycerolipids, particularly triacyclglycerols, increased while cell size decreased under N-and NP-nutrient limited cultures, across all Symbiodiniaceae species. Plimitation caused a decrease in phosphatidylcholine, an important membrane lipid, and saw an increase in isoprenol lipids. This suggests a diversion of phosphorus from phospholipid membranes to the biosynthesis of membrane-stabilizing isoprenes. Reduced photophysiology under P-limitation in all Symbiodiniaceae further supports evidence that P-limitation induced stress in these Symbiodiniaceae cells. As expected, growth rate was reduced in all Symbiodiniaceae at temperature extremes (31 ºC). Significant increases in oxidized lipids, particularly oxidized phosphatidylinositol, and a reduction in ether-linked phospholipids in cultures grown at 31 ºC, suggests increased reactive oxygen species (ROS) abundance in these cells. In addition, at 31 ºC, D. trenchii and both C. goreaui spp. cell size increased, a common sign of ROS accumulation, cell cycle arrest and necrosis. The observed increases in lipid energy storage (triacylglycerols and isoprenoids) under nutrient stress, as well as ROSmitigation via lipid remodeling leading to increases in saturated fatty acids and oxidized lipids under temperatures stress, suggest Symbiodiniaceae can remodel their lipids to adapt to environmental shifts. If similar mechanisms occur in hospite, this could be an adaptive strategy for coral holobionts under a changing climate.